Palm oil mill effluent treatment towards zero discharge - Kathiravale, Sivapalan; Ripin, Adnan (1997)
This study will concentrate on treating the POME by employing a combination of evaporation and adsorption techniques under vacuum condition. The raw effluent has a temperature of 80-85C, thus by introducing a vacuum of 350mm Hg, the effluent will evaporate without any addition of heat. Next, the adsorption process was carried out using four different types of adsorbent's in the vapour phase. Lastly the experiment was also carried out in a pilot plant scale. The distillate (before adsorption) when analysed showed a 99% removal of most polluting parameters monitored except for pH, COD and BOD. This was tackled by the adsorption which further reduced the pH, COD and BOD values. The effluent was able to be concentrated to as high as 25% solid content from the initial content of 3-5% solids. This will result in a recovery of 80% of the water content and also the POME volume will reduce by the same percentage. The concentrated effluent analysis showed a high content of nitrogen, phosphorus and potassium which can be used as feed material for the making of fertiliser. Lastly the pilot plant scale experiments were done and the analysis showed the same results as the bench scale.